No coração da metrópole: as linguagens da cultura em narrativas audiovisuais de jovens das periferias de São Paulo - Arruda, André Ribeiro Passos de (2015)
This research looks at the processes of construction of youth identities. We intend to reflect on the various mechanisms of cultural and political action promoted through media resources, mobilized by young participants of audiovisual creation workshops in civil society organizations, in the suburbs of São Paulo City nowadays. The daily experiments made by these young people through audiovisual recordings, in multiplier institutions which provide them with the knowledge and tools needed, contribute to promoting changes in personal relationships, sociability values as well as to a redefinition of identities day by day. These young people, in varying degrees of organization, build collective identities, get organized in a spirit of solidarity, hold dialogues, recognize themselves as entitled to rights and also as citizens and agents of change in society. We attempted to use an interdisciplinary methodological approach in a perspective related to topics of the areas of Cultural Studies, Anthropology, Discourse Analysis, Languages, History and Sociology, with regard to the dynamics of identity construction processes and social interaction, and urban sociability, for they question the different forms of resistance, as well as the process through which new values, behaviors, identities, new forms of political and cultural action are built.